Protective effects of L-Carnitine and kiwifruit extract against benzo[a]pyrene-induced testicular toxicity in Sprague-Dawley rats - MM Nawaf; LH Ali; Nafi Saud (Babcock University Medical Journal, 2025)
Objective: Benzo[a]pyrene (BaP) is a widespread environmental pollutant known to impair testicular structure and function. This study evaluates whether L-carnitine and kiwifruit extract can protect against BaP-induced testicular toxicity in adult male albino rats.